PRKCSH enhances colorectal cancer radioresistance via IRE1α/XBP1s-mediated DNA repair - Hui Shen; Jing Jin; Nanxi Yu; Tingting Liu; Yongzhan Nie; Zhijie Wan; Yuanyuan Chen; Kun Cao; Ying Xu; Yijuan Huang; Chao Feng; Ruixue Huang; et al. (Cell Death and Disease)
Abstract Neoadjuvant radiotherapy is the standard treatment for locally advanced rectal cancer, but resistance to this therapy remains a significant clinical challenge. Understanding the molecular mechanisms of radioresistance and developing strategies to enhance radiosensitivity are crucial for improving treatment outcomes. This study investigated the role of PRKCSH in colorectal cancer radioresistance and its underlying mechanisms. Our results demonstrate that PRKCSH is upregulated in colorectal cancer cells following ionizing radiation. Inhibiting PRKCSH sensitized these cells to radiation by reducing clonogenic survival, promoting apoptosis, and impairing DNA damage repair. Mechanistically, PRKCSH inhibition reduced p53 ubiquitination and degradation by activating the ER stress IRE1α/XBP1s pathway after radiation exposure, which enhanced DNA repair and contributed to radioresistance. In preclinical CRC models, PRKCSH depletion suppressed tumor growth and increased radiosensitivity. Similarly, in patient-derived organoid models, PRKCSH knockdown reduced organoid growth post-radiotherapy. In rectal cancer patients receiving neoadjuvant radiotherapy, higher PRKCSH expression in post-treatment samples correlated with reduced tumor regression. These findings suggest that targeting PRKCSH diminishes radioresistance by impairing DNA repair through the modulation of ER stress. Furthermore, PRKCSH expression may serve as a biomarker for evaluating radiotherapy efficacy and clinical outcomes in rectal cancer patients undergoing neoadjuvant therapy.